Tracking stimulus representation across a 2-back visual working memory task. Issue 8 (5th August 2020) - Wan, Quan; Cai, Ying; Samaha, Jason; Postle, Bradley R.
Abstract : How does the neural representation of visual working memory content vary with behavioural priority? To address this, we recorded electroencephalography (EEG) while subjects performed a continuous-performance 2-back working memory task with oriented-grating stimuli. We tracked the transition of the neural representation of an item ( n ) from its initial encoding, to the status of 'unprioritized memory item' (UMI), and back to 'prioritized memory item', with multivariate inverted encoding modelling. Results showed that the representational format was remapped from its initially encoded format into a distinctive 'opposite' representational format when it became a UMI and then mapped back into its initial format when subsequently prioritized in anticipation of its comparison with item n + 2. Thus, contrary to the default assumption that the activity representing an item in working memory might simply get weaker when it is deprioritized, it may be that a process of priority-based remapping helps to protect remembered information when it is not in the focus of attention.